Enhancement of Nucleate Pool Boiling Heat Transfer with Sodium Oleate - Ahmmed, KM Tanvir; Syeda, Sultana Razia (Journal of Chemical Engineering, 2017)
In this study saturated nucleate pool boiling of water with sodium oleate surfactant on a horizontal cylindrical heater surface has been investigated experimentally and compared with that of demineralized water. The concentration of sodium oleate in water was 100-300 ppm. The experimental results show that a small amount of surfactant enhances the heat transfer coefficient significantly. At low surfactant concentrations, heat transfer coefficient increases with increasing surfactant concentration in water. The maximum heat transfer enhancement is found to be at 250 ppm of sodium oleate solution. By adding more surfactant to water, heat transfer coefficient is found to be lowered. Surface tension of different concentration of sodium oleate solutions is measured. It is observed that the maximum heat transfer coefficient is obtained at a surfactant concentration that corresponds to the critical micelle concentration (cmc) of the sodium oleate solution. Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 44-48